2004
DOI: 10.1113/jphysiol.2004.072033
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia enhances cat chemosensory and ventilatory responses to hypoxia

Abstract: The carotid body (CB) chemoreceptors may play an important role in the enhanced hypoxic ventilatory response induced by chronic intermittent hypoxia (CIH). We studied the effects of cyclic hypoxic episodes of short duration on cat cardiorespiratory reflexes, heart rate variability, and CB chemosensory activity. Cats were exposed to cyclic hypoxic episodes (P O 2 ∼ 75 Torr) repeated during 8 h for 2-4 days. Cats were anaesthetized with sodium pentobarbitone (40 mg kg −1 I.P., followed by 8-12 mg I.V.), and vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
189
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 187 publications
(210 citation statements)
references
References 43 publications
16
189
0
5
Order By: Relevance
“…enhances CB chemosensory discharge in normoxia and in response to hypoxia. 12,19,[23][24][25] Furthermore, it has been shown that arterial blood pressure (BP) rapidly increases after 3 to 4 days after CIH exposure, 14,[26][27][28] which is consistent with the time required to potentiate the neural discharges from the CB chemoreceptor during CIH .…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…enhances CB chemosensory discharge in normoxia and in response to hypoxia. 12,19,[23][24][25] Furthermore, it has been shown that arterial blood pressure (BP) rapidly increases after 3 to 4 days after CIH exposure, 14,[26][27][28] which is consistent with the time required to potentiate the neural discharges from the CB chemoreceptor during CIH .…”
mentioning
confidence: 66%
“…12,13,19,30 In addition, we studied the effects of the β-adrenergic and cholinergic receptors blockers on resting HR to determine the sympathovagal control to the heart.…”
Section: Cardiac Autonomic Balancementioning
confidence: 99%
See 3 more Smart Citations